Teacher educators as gatekeepers: Preparing the next generation of teachers for technology integration in education - Tondeur, Jo; Scherer, Ronny; Baran, Evrim; Siddiq, Fazilat; Valtonen, Teemu; Sointu, Erkko (British journal of educational technology, 2019)
This study aims at investigating the profiles of teacher educators in order to explore their ability to prepare preservice teachers for technology integration in education. Specifically, the current study examines whether teacher educators can be grouped on the basis of their attitudes toward ICT (in education), their ICT self‐efficacy to design ICT‐rich learning environments, their competencies to use ICT in their teaching practice and the strategies they use to prepare preservice teachers for technology integration. These strategies are included in the SQD (Synthesis of Qualitative Data) model and comprise: (1) teacher educators as role models, (2) reflecting on the role of technology in education, (3) learning how to use technology by design, (4) collaboration with peers, (5) scaffolding authentic technology experiences and (6) providing continuous feedback. Data were collected from a sample of 284 teacher educators in Flanders, the Dutch‐speaking part of Belgium, and submitted to latent profile analysis. The added value of the current study lies in the account of how SQD strategies and a typical set of determinants of ICT integration can be associated within teacher educators’ profile. Based on the profiles emerging from this study, teacher training institutions should consider their teacher educators to be gatekeepers when preparing future generations of teachers for the learning environments of the twenty‐first century. In the discussion section, the implications for practice and future research are discussed.